(untitled) (Educational Knowledge, 2016)
This explanatory research was conducted to analyze the teaching methodologies implemented in initial teacher training at Higher Education Institutions in Western El Salvador, as well as their effectiveness. To this end, interviews were conducted with faculty members from the three universities participating in the study. The study revealed that faculty members determine which methods, techniques, and resources to apply based on the objectives set. This is reflected in the level of student attention and participation. It should be noted that the effectiveness of this approach depends not only on the methodological aspects of the process but also on various factors—academic, personal, and social—which, in some cases, prevent students from fully achieving the stated objectives.